Reductive alkylation of hyaluronic acid for the synthesis of biocompatible hydrogels by click chemistry - Huerta-Angeles, Gloria; Němcová, Miroslava; Příkopová, Eva; Šmejkalová, Daniela; Pravda, Martin; Kučera, Lukáš; Velebný, Vladimír (Carbohydrate polymers, 2012)
Hyaluronan (HA) based hydrogels have been synthesized combining chemical modification of the polysaccharide by partial oxidation, reductive amination and 'click chemistry'. HA was oxidized by 4-acetamido-TEMPO-mediated reaction, using sodium hypochlorite as primary oxidant and NaBr in buffered pH, so that the produced aldehyde moieties (hemiacetals) were trapped in situ by adding primary amines containing azide or alkyne-terminal groups. The structure of the reaction products, oxidized-HA and primary amines bonded to HA, was elucidated using 2D NMR spectroscopy. SEC-MALLS analysis of the modified substrates showed a negligible degradation of the polysaccharide using this procedure. Furthermore, azido- and alkynyl derivatives underwent cross-linking by click chemistry into hydrogels, which were characterized by NMR, FT-IR, swelling degree and mechanical properties. Possible application of the material as scaffold for tissue engineering was tested by seeding and proliferation of chondrocytes for up to 15 days.
Keywords: Cell Survival; Cross-Linking Reagents; Tissue Engineering; Humans; reologie; tkáňové inženýrství; hydrogely; Click Chemistry; alkylace; Alkylation; click chemie; lidé; Rheology; reagencia zkříženě vázaná; Cells, Cultured; proliferace buněk; chondrocyty; Biocompatible Materials; kultivované buňky; Cell Proliferation; kyselina hyaluronová; Hydrogels; biokompatibilní materiály; Chondrocytes; Hyaluronic Acid; viabilita buněk